Effects of different levels of fenofibrate on sensory properties and fatty acids profile of breast meat of broilers - Azizi-Chekosari, Maryam (Array, 2020)
The present study was performed to evaluate the effects of different levels of fenofibrate on the characteristics of broiler meat in a completely randomized design with 3 treatments, 4 replicates and 10 oneday- old male Ross 308 strain chicks per replicate for 42 days. Experimental treatments included 3 levels of fenofibrate (0, 50, and 100 mg/kg), which were used in combination with the basal diet. Analysis of the effect of experimental treatments was performed by SAS statistical software and the comparison of the means at 5% probability level with Duncan's multiple-range test. The results showed that consumption of fenofibrate improved the flavor characteristics of breast meat and the flavor of breast meat increased significantly with the application of 100 mg/kg fenofibrate compared to the control (P<0.05). Consumption of fenofibrate increased the percentage of oleic acid and linoleic acid and decreased saturated fatty acids, including palmitic acid and stearic acid in breast meat.